Coccidioidomycosis Dynamics in Relation to Climate in the Southwestern United States. Issue 1 (15th January 2018) - Gorris, M. E.; Cat, L. A.; Zender, C. S.; Treseder, K. K.; Randerson, J. T.
Abstract: Valley fever is endemic to the southwestern United States. Humans contract this fungal disease by inhaling spores of Coccidioides spp. Changes in the environment can influence the abundance and dispersal of Coccidioides spp., causing fluctuations in valley fever incidence. We combined county‐level case records from state health agencies to create a regional valley fever database for the southwestern United States, including Arizona, California, Nevada, New Mexico, and Utah. We used this data set to explore how environmental factors influenced the spatial pattern and temporal dynamics of valley fever incidence during 2000–2015. We compiled climate and environmental geospatial data sets from multiple sources to compare with valley fever incidence. These variables included air temperature, precipitation, soil moisture, surface dust concentration, normalized difference vegetation index, and cropland area. We found that valley fever incidence was greater in areas with warmer air temperatures and drier soils. The mean annual cycle of incidence varied throughout the southwestern United States and peaked following periods of low precipitation and soil moisture. From year‐to‐year, however, autumn incidence was higher following cooler, wetter, and productive springs in the San Joaquin Valley of California. In southcentral Arizona, incidence increased significantly through time. By 2015, incidence in this region was more than double the rate in the San Joaquin Valley. Our analysis provides a framework for interpreting the influence of climate change on valley fever incidence dynamics. Our results may allow the U.S. Centers for Disease Control and Prevention to improve their estimates of the spatial pattern and intensity of valley fever endemicity. Plain Language Summary: Valley fever is a fungal disease most common in the southwestern United States. People become sick with valley fever when they inhale fungal spores called Coccidioides . Climate and human activity can change both the amount of fungal spores and when these spores enter the air. This leads to fluctuations in the number of valley fever cases. We created a valley fever database for the southwestern United States to explore how climate and human factors determine the areas and time of year with the highest number of valley fever cases. We found that more people become sick with valley fever in areas with warmer temperatures and drier soils. The month with the highest number of cases varied across the southwestern United States. Also, cases were high after very dry conditions. Using our database, we found two main hot spots for valley fever: the San Joaquin Valley of California and southcentral Arizona. By 2015, southcentral Arizona had the highest number of valley fever cases in the entire country, more than double the amount in the San Joaquin Valley. Our results will help determine what new communities may be at risk for valley fever in the future, so that doctors and citizens can prepare in advance. Key Points: We created a valley fever database for the southwestern United States and explored the climate factors influencing the dynamics of disease incidence Incidence was higher in areas with warmer air temperatures and drier soils and seasonal peaks followed periods of low environmental moisture Our results may improve estimates of valley fever endemicity and aid future analysis of global change and valley fever incidence dynamics